K.H. Ahmad Dahlan : Pemikiran dan Perjuangan dalam Pembaharuan Pendidikan Islam - Karenza Balqis Putri Kurnia; Muhamad Amar Fadil; Inara Sasikirana; Evi Savitri; Ferdinan Budiaji Pradana; Astika Nurul Hidayah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Education plays an important role in building a generation that is intelligent, virtuous, and capable of facing the challenges of the times. However, education cannot be separated from social and cultural factors, where social and cultural conditions themselves have an impact on education. One such case occurred during the colonial era, when the colonial government had a significant influence in shaping the educational system in Indonesia at that time. Education was essentially divided into two: formal school education, which focused only on worldly knowledge, and education in pesantren (Islamic boarding schools), which taught only religious knowledge. Due to this situation, K.H. Ahmad Dahlan was moved to reform Islamic education. This research aims to explore K.H. Ahmad Dahlan's thoughts on education and to understand his efforts in the process of reforming Islamic education. The research uses a literature study method, where data is obtained from writings such as books, journal articles, and other supporting texts related to the issue. The results of the study show that K.H. Ahmad Dahlan had his own educational philosophy, in which religious knowledge and worldly knowledge were seen as an integrated whole. K.H. Ahmad Dahlan’s struggle can be seen from his efforts to establish a school that integrated both religious and worldly knowledge. His contribution to educational reform is still felt today, as educational institutions under Muhammadiyah have spread across Indonesia. Muhammadiyah itself is an organization founded by K.H. Ahmad Dahlan, which serves as a platform or means for his struggle.